The Incidence and Severity of Downy Mildew Disease on Local Madurese Maize Crops in Sumenep district, East Java, Indonesia - Syaiful Khoiri; Abdiatun Abdiatun; Khairatul Muhlisa; Achmad Amzeri; Dita Megasari (Faculty of Agriculture, Pattimura University, 2021)
In Madura island, corn is the main commodity that is widely planted with an area of 301,725 ha or about 30% of the area of maize in East Java. Madura Island has local cultivars, such as: Tambin, Talango, Guluk-guluk, Manding, and Kretek. Efforts to increase production are continuously being made, starting from improving varieties until managing plant pests. One of the main diseases in maize is downy mildew. However, information about the incidence, incidence, severity, and species that cause downy mildew in local cultivars has not been reported. So, this study aims to identify the causes of downy mildew in local cultivars of Madura and disease severity in the field. The research method is a survey on local maize centers. Sampling was done by using the diagonal sampling method. Each plant sample was observed for symptoms of disease and scoring to calculate the value of disease severity. Fungi identification was carried out by microscopic observation of the fungus. The results showed that the cause of downy mildew in Madura local maize in Sumenep Regency was P. maydis. The highest incidence, disease severity, and AUDPC value after 4 MST were found in Guluk-guluk cultivars in Padangdangan Village, but had the lowest disease progression rate values. Meanwhile, the highest rate of disease progression was found in the Manding cultivar in Mandala Village. Based on the resistance category, Talango cultivar had the best resistance when compared to other cultiva.Keywords: AUDPC, downy mildew, disease progress, Madurese maize, Peronosclerospora maydis